SIMPORA: An Android-Based Data Management and Analytics Framework for Enhancing Community Sports Ecosystems - Edi Purwanto; Heny Setyawati; Cahyo Yuwono (Science and Technology Research Centre Universitas PGRI Semarang, 2026)
The increasing adoption of digital technologies in sports management highlights the need for efficient, data-driven systems that enhance community engagement and program evaluation. However, regional sports organizations in Indonesia, such as the Central Java Regional Indonesian Sports Community (KORMI), still face challenges in data integration, monitoring, and communication across stakeholders. This study aimed to design and evaluate SIMPORA, an Android-based data management and analytics system that supports sports activists, trainers, and administrators in planning, monitoring, and evaluating community sports programs. Using a Research and Development (R&D) approach with the Agile development model, the system was developed and tested among 45 users, including community sports leaders and KORMI administrators. Instruments included usability testing (System Usability Scale), task completion efficiency, and user satisfaction surveys. Quantitative evaluation results showed a mean usability score of 84 (excellent category), a 27% increase in data recording accuracy, and a 34% improvement in communication efficiency compared to manual reporting. User satisfaction reached 91%, indicating strong acceptance of the system. These findings demonstrate that SIMPORA effectively facilitates real-time data-driven decision-making and enhances coordination within community sports ecosystems. The system offers practical implications for expanding digital transformation initiatives in sports management across regional and national contexts.